Coronary artery bypass grafting in women and its impacts - Ribeiro, Ana Beatriz Monserrath Antenor; Moraes, Mickaelle Caroline Ferreira; Almeida, Rodolfo Passos; André, Maria Eduarda Guizelini (Seven Editora, 2024)
Myocardial revascularization, a crucial surgical procedure for patients with obstructive coronary artery disease, has a significant impact on public health, especially in Brazil. Although historically most patients have been men, women are increasingly requiring this procedure, due to factors such as hormonal changes and specific cardiovascular risk. Studies indicate that women have higher mortality rates after surgery, which underscores the importance of specialized monitoring and a personalized approach. Understanding the specific risks and promoting healthy habits are essential to improve outcomes in women undergoing coronary artery bypass grafting. DOI:https://doi.org/10.56238/sevened2024.025-007